2016
DOI: 10.1016/j.renene.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temperature and efficiency in relation to mass flow on a solar flat plate collector in Mexico

Abstract: a b s t r a c tThis study presents the thermal analysis of a solar flat plate water heater working under real operating conditions in a hot sub-humid region, in the city of Merida, Yucatan, Mexico. This water heater was evaluated under thermosyphon conditions and, with the use of a submersible pump, under forced flow conditions. In both cases the thermal performance of the collector was studied in order to determine the impact of flow on the working temperature and efficiency of the collector.A comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Solar energy can be used in a variety of ways. Solar heat may be utilized for various applications, including space heating, household hot water, cooling, and even process heating 4,5 . Solar energy collection and conversion is a www.nature.com/scientificreports/ GNPs based nanofluid.…”
Section: Exergy Efficiency ηmentioning
confidence: 99%
“…Solar energy can be used in a variety of ways. Solar heat may be utilized for various applications, including space heating, household hot water, cooling, and even process heating 4,5 . Solar energy collection and conversion is a www.nature.com/scientificreports/ GNPs based nanofluid.…”
Section: Exergy Efficiency ηmentioning
confidence: 99%
“…At 10° angle, 47.64%, 50.0%, and 51.17% efficiencies were noted for three different cases. Using a submersible pump and forced flow conditions, Diego‐Ayala and Carrillo 16 assessed the temperature and efficiency of FPSC for three different thermo‐syphon conditions. They concluded that by controlling the maximum working temperature with a forced flow condition led to an increased efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Their research showed that this approach led to an increase in annual energy savings (up to 95.8% for zone 1; 91.3% for zone 2; 81% for zone 3; 74% for zone 4). An investigation of the impact of flow on both the working fluid temperature and the collector efficiency was carried out by Diego-Ayala et al [32]. They conducted thermal analysis of a solar flat plate water heater in a hot sub-humid region (Yucatan, Mexico).…”
Section: Introductionmentioning
confidence: 99%